Hess J1731-347 is likely a quark star based on the density-dependent vMIT bag model - Min Ju; Pengcheng Chu; Xuhao Wu; He Liu (European Physical Journal C: Particles and Fields)
Abstract In this study, we extend the MIT bag model by incorporating the vector interaction among quarks and introducing a density-dependent bag pressure. Then we proceed to investigate the thermodynamic properties of strange quark matter (SQM) and pure up-down quark matter (udQM) in quark stars (QSs). Our findings demonstrate that the density dependence of bag pressure $$B(n_b)$$ B ( n b ) and the vector interaction $$G_V$$ G V among quarks can significantly stiffen the equation of state (EOS) for both SQM and udQM which allows for the description of massive compact stars such as those observed in GW190814 and PSR J0740+6620 as plausible candidates for QSs. Ultimately, we derived a series of mass–radius relations of QS based on several combinations of ( $$B_{as}$$ B as , $$β $$ β ). Our results support the hypothesis that HESS J1731-347 is a quark star.